Surgical suturing-induced melanocytic nevi. A new type of eruptive melanocytic nevi? - Katoulis, Alexander C. (J Dermatol Case Rep, 2016)
BACKGROUND: Nevogenesis is a complex process involving several pathogenetic mechanisms, including genetic factors, hormonal influences and UV-radiation. Trauma has been described as a triggering factor for an alternative pathway of nevogenesis. Eruptive melanocytic nevi (EMN), related either to immunosuppression or to blistering disorders, represent a special type of nevi probably induced by the disruption of the dermo-epidermal junction and consequent proliferation of quiescent pigment cells during re-epithelization. MAIN OBSERVATIONS: We report two patients with three melanocytic nevi that developed de novo along the direction of surgical suturing, following surgical operation for other reason. The lesions exhibited special dermoscopic characteristics and histology revealed features of acquired melanocytic nevi. CONCLUSIONS: Such cases may represent a new type of eruptive nevus, the surgical suturing-induced nevus, which should be included in the differential diagnosis of new pigmentation developing within a scar.